Bank Accounting and Audit (Texas Journal of Multidisciplinary Studies, 2022)
This article clearly defines what the terms “bank accounting” and “audit” mean and how important they are to keep banking system work pertinently for customers. It gives relevant information about banking system and proves the vey information mentioned in detail providing the sources and academic researches.